2017
DOI: 10.1038/s41598-017-05270-8
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Chickens Expressing the 3D8 Single Chain Variable Fragment Protein Suppress Avian Influenza Transmission

Abstract: The 3D8 single chain variable fragment (scFv) is a mini-antibody that causes unusual sequence-independent nuclease activity against all types of nucleic acids. We used recombinant lentiviruses to generate transgenic chickens expressing the 3D8 scFv gene under the control of the chicken β-actin promoter. From 420 injected embryos, 200 chicks (G0) hatched and were screened for the 3D8 scFv using PCR, and 15 chicks were identified as transgenic birds expressing the transgene in their semen. The G0 founder birds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 35 publications
1
25
0
1
Order By: Relevance
“…Although birds were not resistant to initial infection, viral transmission was prevented (Lyall et al, 2011 ). A different study demonstrated the possibility to suppress influenza A virus transmission in transgenic birds expressing the 3D8 single chain variable fragment (scFv), a gene that interacts with viral genome leading to suppression of viral shedding (June Byun et al, 2017 ).…”
Section: Generation Of Genetically Modified Chickensmentioning
confidence: 99%
“…Although birds were not resistant to initial infection, viral transmission was prevented (Lyall et al, 2011 ). A different study demonstrated the possibility to suppress influenza A virus transmission in transgenic birds expressing the 3D8 single chain variable fragment (scFv), a gene that interacts with viral genome leading to suppression of viral shedding (June Byun et al, 2017 ).…”
Section: Generation Of Genetically Modified Chickensmentioning
confidence: 99%
“…The viability of using a transgenic approach to protect against LPAI was subsequently addressed by Byun and colleagues [ 20 ]. In these studies, chicken were engineered to express the 3D8 single chain variable Fragment (scFv) customised to have an affinity for the IAV nuceloprotein.…”
Section: Genetically Modified Chickens Resistant To Avian Influenzmentioning
confidence: 99%
“…In these studies, chicken were engineered to express the 3D8 single chain variable Fragment (scFv) customised to have an affinity for the IAV nuceloprotein. scFv was of particular interest as it causes nuclease activity and has displayed hydrolytic activity against both RNA and DNA viruses [ 20 ]. Following direct infection with LPAI A/Korean native chicken/Korea/K040110/2010(H9N2), scFv transgenic chickens did not display any difference in oropharyngeal shedding when compared to their non-transgenic counterparts [ 20 ].…”
Section: Genetically Modified Chickens Resistant To Avian Influenzmentioning
confidence: 99%
“…As a result of a highly efficient genome modification capacity, these viral systems have also been used for avian transgenesis. After the first studies of transgenic animal production by retroviral infection in Eyal giladi and Kochav (EG&K) stage X chicken embryos, diverse transgenic birds have been successfully established for a variety of purposes, including functional protein expression and the development of model animals [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Specifically, mass production of functional proteins using retroviral systems in serum and egg whites of transgenic chickens suggests its practical use as a bioreactor system, although the silencing of transgenes was observed in the subsequent generation (~5.6 mg/mL) [ 22 ].…”
Section: Development Of Transgenic Technologies and Application Fomentioning
confidence: 99%